Association between oxidative stress exposure and colorectal cancer risk in 98,395 participants: results from a prospective study - Gu, Haitao; Li, Bo; Xiang, Ling; Xu, Zhiquan; Tang, Yunhao; Zhu, Zhiyong; Jiang, Yahui; Peng, Linglong; He, Hongmei; Wang, Yaxu (Frontiers in Nutrition, 2023)
The intricate role of oxidative stress (OS) in colorectal cancer (CRC) initiation is underscored by an imbalance between pro-oxidants and antioxidants. Utilizing the Oxidative Balance Score (OBS) as a metric, this study aims to investigate the association between OS exposure and CRC risk, while also examining potential sex-specific differences in a large U.S. cohort.The study included 98,395 adults from the Prostate, Lung, Colorectal, and Ovarian (PLCO) Cancer Screening Trial. To construct the OBS, 14 dietary and lifestyle factors intricately associated with oxidative stress were quantified. A higher OBS value indicated a more favorable oxidative balance pattern or diminished OS exposure. Due to sex-specific differences in OBS, associations were evaluated separately for men and women based on Cox regression analysis.Subgroup analyses were conducted to elucidate potential modifiers.Results: During 867,963.4 person-years of follow-up, 1054 CRCs occurred. The mean (SD) age and OBS were 65.52 (5.73) years and 14.09 (3.95) points, respectively. In the fully adjusted Cox model, we observed an inverse association between OBS and CRC incidence in women (HRQ5 vs Q1: 0.72; 95% CI: 0.52, 0.99; P for trend = 0.018) but not men. Subgroup analyses revealed the inverse association was more pronounced among women without versus with a family history of CRC (HRQ5 vs Q1: 0.66, 95% CI: 0.47-0.93; P for trend = 0.001; P for interaction = 0.001). The results remained robust after several sensitivity analyses.Higher OBS was associated with lower CRC risk in women but not men; this inverse association was stronger among women without a family history of CRC. These findings suggest exposure to OS may confer sex-specific CRC risk effects, especially for women without a family history of CRC.